Feedback received and role performance: The mediating role of engagement and the moderating role of authentic living - Chinelato, R. S. de C.; Ferreira, M. C.; Valentini, F.; Tavares, S. M. de O. e M. (Ciencias Psicológicas, 2024)
This research aims to identify the moderating role of authentic living in the relationship between feedback received and role performance, mediated by work engagement. The data were based on a convenience sample of Brazilian workers from public and private organizations (N=1,244). The significant interaction between the feedback and authentic living allowed us to understand that the main effects of feedback on performance take place in individuals with high authentic living. When individuals are more authentic, the information they receive about their performance more strongly affects the motivational process at work itself. This study highlights the positive relationship between work and personal resources, as well as the work engagement and performance on the other, thus contributing to increase the feedback the organizations receive about performance, as well as to create environments that facilitate authenticity.